PENGARUH BUDAYA TOLERANSI KEKUASAAN TERHADAP PERSEPSI KARIR BIROKRATIK DAN PROFESIONAL - Rahayuningsih, Sri; Rijanti, Tristiana; Indriyaningrum, Kis (Proceeding Fakultas Ekonomi, 2014)
Organization culture is collection of positive value that is useful for organization in order to influence behavior. Authority tolerance culture is part of culture concept founded by Hofstade (1994). As high as authority to culture, means they are willing to accept the authority to culture difference in an organization Career perception as long as working (Asthur, et al 1989).The aim of this research are to analyze and to prove wheather tolerant culture influence bureaucratic and professional career perception. Method of this research uses purposive sampling method with 89 female nurse as sample and also usess doble regression analysis. Result of this research shows that authority tolerance culture has positive influence towards bureaucratic to career perception and professional career perception. It means that as high as authority tolerance culture will determine life some oneâs career choice, even though still in perception form. Next, this perception will influence some oneâs behavior in acting to do pioneering career. Keyword : Authority tolerance culture, Bureaucratic Career Perception, Professional Career Perception Profesiional Career Perception.